The Origins Of Psychological Conflict In Classical And Early Modern Literature (Journal of Advances and Scholarly Researches in Allied Education, 2025)
This paper analyzes the portrayal of mental health, emotional turmoil, and the inner conflicts of characters in notable literary works across different periods. It focuses on the impact of various psychological theories, such as Freudian psychoanalysis and existentialist psychology, on character development and plot construction. Repression does not eradicate our anxieties, agonies, and urges; rather, it empowers them by enabling them to shape our present experience. Under a related process known as Sublimation, the suppressed content is elevated to a higher level or camouflaged as something honorable. Oedipus disdained the gods' oracles and prophesies. The more skilled the artist is, the more realistic and engaging the characters, plot points, and conflicts may be, and the more the reader will be captivated by them because of the illusion of authenticity.